KEABSAHAN PERJANJIAN ARBITRASE ASIMETRIS BERDASARKAN HUKUM INTERNASIONAL - Purkon Abdul Latip (Faculty of Law Universitas Sebelas Maret, 2023)
This research analyzes the problem of the validity of an asymmetrical arbitration agreement in international commercial arbitrations based on international law such as the New York Convention, the UNCITRAL Model Law and the principle of general law. This research is normative legal research. Data used secondary one including primary legal materials, secondary, and tertiary ones. The data collection technique used library research, and deductive logic data as an analysis techniques. The results show that the validity of the arbitration agreement is influenced by the national law governing the agreement between the parties, the national law where the place where an award is made and will be enforced as it in accordance with the New York Convention, and the UNCITRAL Model Law provisions. Thus, each jurisdiction will have different considerations and decisions in granting the validity of the asymmetric arbitration agreement as it influenced by the principle of general law interpretation each jurisdiction.